The mapping of science teacher candidate’s prior knowledge in cellular respiration topic - Dewi, Safira Permata; Zen, Djunaidah; Haryani, Maefa Eka (University of Muhammadiyah Malang, 2019)
The proper learning strategy, mainly in cellular respiration topic, can be determined as mapping teacher candidate?s prior knowledge was done. This study aimed to get the profile of prior knowledge of teacher candidates in cellular respiration topic. This survey research used four-tier diagnostic test as data collection instrument. The number of samples was 183 of teacher candidates from three study programs in Faculty of Teacher Training and Education, Universitas Sriwijaya. The data was analyzed using percentage. The results showed that the best understanding of the concept was in the utilization of carbohydrates, proteins, and fats during cellular respiration process. The highest misconception tended to occur in general concept of cellular respiration. Thus, the studies which emphasize the undergirding reasons of the high misconception occurred.